Nutrient Limitation in Central Red Sea Mangroves - Almahasheer, Hanan; Duarte, Carlos M.; Irigoien, Xabier (Frontiers in Marine Science, 2016)
As coastal plants that can survive in salt water, mangroves play an essential role in large marine ecosystems (LMEs). The Red Sea, where the growth of mangroves is stunted, is one of the least studied LMEs in the world. Mangroves along the Central Red Sea have characteristic heights of ~2 m, suggesting nutrient limitation. We assessed the nutrient status of mangrove stands in the Central Red Sea and conducted a fertilization experiment (N, P and Fe and various combinations thereof) on four-week-old seedlings of Avicennia marina to identify limiting nutrients and stoichiometric effects. We measured height, number of leaves, number of nodes and root development at different time periods as well as the leaf content of C, N, P, Fe and Chl a in the experimental seedlings. Height, number of nodes and number of leaves differed significantly among treatments. Iron treatment resulted in significantly taller plants compared with other nutrients, demonstrating that iron is the primary limiting nutrient in the tested mangrove population and confirming Liebig’s law of the minimum: iron addition alone yielded results comparable to those using complete fertilizer. This result is consistent with the biogenic nature of the sediments in the Red Sea, which are dominated by carbonates, and the lack of riverine sources of iron.